La introduccion de especies vegetales y la valoracion del riesgo de que se conviertan en malas hierbas - Del Monte, J.P.=700 1 Zaragoza, C.
(Es, En)
ilus., 34 ref.
Keywords: FLORA; ESPECIES; VEGETALES; RIESGO; ESPAÑA; ESPECIES ALOCTONAS; EXOTICAS; INVASORAS; NATURALIZADAS